Rethinking Gender and Power: A Limitation of Women's Freedom in Accidental Transients by Randa Jarrar - Ni’mah, Ima Fauzia; Munawwaroh, Nurul; Fitria, Sari (English Language and Literature, 2024)
This article aims to explore the relationship between gender and power in the short story, Accidental Transients, by Randa Jarrar. It discusses how women’s freedom is limited in a patriarchal society. In this kind of society, there is male supremacy which places men as the superior one. This study applied feminist existentialist concept by Simone de Beauvoir. It engages with an idea that women have to be able to become subjects in order to be not dominated by men. Furthermore, this study employs content analysis method. The data used in this study are sentences that show the issue of gender and power in Accidental Transients written by Randa Jarrar. The results of this study show that the main character, Dina, in patriarchal life is burdened by her gender role to be responsible for domestic tasks. In addition, she also does not have the freedom to act as she intends. Dina's character in this story shows that male dominance over women is still difficult to eliminate in a patriarchal society.